Verifying documentation form for Peregrine Falcon sighting submitted by Thomas Stone, December 27 1980 - Stone, Tomet al (1980)
A form documenting the sighting of a Peregrine Falcon in Cedar Falls submitted by Thomas Stone. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1980-1981. Epson - sheet feed/flatbed